Current sensor performance improvement method based on magnetic coupling agent

By using magnetic coupling agent in the current sensor, the problems of poor magnetic circuit contact and magnetic resistance change noise are solved, and high-precision and high stability measurement of the current sensor is achieved, adapting to different application scenarios and environmental conditions, and extending the service life of the sensor.

CN119902143AActive Publication Date: 2025-04-29BEIJING JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411813884.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-29
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Existing current sensors are prone to poor magnetic circuit contact and magnetic resistance change noise during long-term use, resulting in a decrease in measurement accuracy and stability, making it difficult to meet the high-precision and high stability requirements of different application scenarios.

Method used

The current sensor performance improvement method based on magnetic coupling agent is adopted. By accurately setting the mechanical performance indicators of the magnetic coupling agent paste, and adjusting them according to the actual application environment and the magnetic circuit characteristics of the sensor, magnetic coupling agent is prepared using silicone oil, thickener and conductive filler, applied to the magnetic circuit contact surface of the current sensor, its weather resistance, corrosion resistance, texture softness and temperature stability are evaluated, and the coupling agent formula is optimized by compensation of mechanical performance strength errors.

Benefits of technology

Effectively suppress magnetic circuit noise, improve the measurement accuracy and stability of the current sensor, adapt to various working environments, including high voltage, low voltage, high temperature, low temperature and other extreme conditions, extend the service life of the sensor and improve its long-term operation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119902143A_ABST
    Figure CN119902143A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the performance of a current sensor based on a magnetic coupling agent, and the method comprises the steps: precisely setting the key mechanical performance indexes of magnetic coupling agent paste, and carrying out the fine regulation and control based on the specific conditions of an actual application environment and the magnetic circuit characteristic type of the sensor; and the key mechanical characteristics such as the hardness and the temperature stability of the paste are widely adjusted. Meanwhile, an environmental adaptability evaluation strategy based on a two-dimensional material scientific characterization technology is introduced, real-time monitoring and optimization of the paste component proportion are realized, and effective suppression of magnetic circuit noise and efficient improvement of the overall performance of the current sensor are ensured. The reduction of the noise directly improves the measurement precision of the current sensor, so that the measurement of current parameters is more accurate and reliable in a complex and changeable power system environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the performance of a current sensor based on a magnetic coupling agent. Background Art

[0002] In the safe and stable operation of the power system, accurate and real-time measurement of current parameters in the circuit is crucial. With the rapid development of smart grid and power electronics technology, current sensors, as core devices for monitoring current size and direction, play an indispensable role in automation equipment, smart grids, new energy vehicles and other fields. However, the accuracy and stability of current sensors directly affect the operating efficiency and safety of the entire power system, especially in complex and changeable application scenarios such as high voltage or low voltage, which places more stringent requirements on the performance of sensors.

[0003] Although the existing current sensor technology has met the basic needs of the power system to a certain extent, it still faces many challenges in practical applications. On the one hand, since the current sensor will experience frequent opening and closing and wear during long-term use, the stability of the internal magnetic circuit closure will gradually decrease, resulting in poor magnetic circuit contact and the generation of magnetic resistance change noise. This magnetic resistance change noise not only increases the uncertainty of the measurement, but also seriously reduces the measurement accuracy and stability of the current sensor. On the other hand, different application scenarios have different performance requirements for current sensors. Traditional current sensors often find it difficult to simultaneously meet the high-precision and high-stability requirements under different environmental conditions.

[0004] In order to improve the measurement accuracy and stability of current sensors, existing technologies have mainly explored aspects such as sensor structure design, material optimization, and signal processing. However, these methods have limited effects and high costs in solving the problems of poor magnetic circuit contact and magnetic resistance change noise. For example, although improving the sensor structure design to enhance the stability of the magnetic circuit can alleviate the problem to a certain extent, it is often accompanied by increased costs and increased complexity; while material optimization is often limited by the inherent characteristics of the material, and it is difficult to achieve all-round performance improvement.

[0005] In summary, the existing technology has obvious shortcomings in solving the problems of poor magnetic circuit contact and magnetic resistance change noise of current sensors. An innovative solution is urgently needed to effectively suppress the magnetic resistance change noise caused by poor magnetic circuit contact, thereby improving the measurement accuracy and stability of the current sensor. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for improving the performance of a current sensor based on a magnetic coupling agent, comprising the following steps: Step 1: Preliminarily calculate the mechanical strength of the coupling agent paste based on the environment and the characteristics of the current sensor type. η ; Among them, Q is the mechanical strength, η is the efficiency adjustment coefficient, 1 is initially the core magnetic permeability η, 2 Initially, the core permeability, B s is the saturation flux density, S is the core cross-sectional area, H c is the coercivity, T is the ambient temperature, T C is Curie temperature, R is ambient humidity, A is vibration amplitude Step 2, preparation of magnetic coupling agent: the magnetic coupling agent includes base oil, thickener, and conductive filler. The specific mechanical properties are determined by experiment using dichotomy method to adjust the filler ratio, and finally the magnetic coupling agent is prepared by mechanical stirring; Step 3: Coupling agent trial and effect evaluation: Apply the prepared coupling agent to the contact surface of the magnetic circuit of the current sensor, evaluate the coupling agent's weather resistance, corrosion resistance, hardness, temperature stability, and magnetic circuit noise suppression effect in actual use, and calculate the mechanical strength error ∆e, whose value is between 0 and 1, which can intuitively reflect the degree of closeness between the actual performance of the coupling agent and the expected target; Step 4: Mechanical property compensation of coupling agent: Add the mechanical property strength error ∆e obtained in step 3 to the mechanical property strength formula established in step 1 to obtain the final mechanical property strength of the coupling agent paste. ; in is the adjustment factor, To compensate for the mechanical strength; According to the compensated mechanical property strength, the coupling agent paste formula is configured through experiments to find the proportion of the corresponding formula ingredients.

[0007] In step 2, silicone oil is selected as the base oil based on its excellent high temperature resistance and excellent corrosion resistance. In order to improve the performance of the base oil, a thickener is introduced for thickening treatment. The thickener refers to a substance that can increase the viscosity of a liquid and turn it into a semi-solid or solid state. In the present invention, the thickener needs to have good heat resistance and chemical stability, so an inorganic thickener, such as fumed silica, is preferably used.

[0008] In step 2, the conductive filler is one or more of ceramic ferrite, graphite, and graphene.

[0009] In step 3, the prepared coupling agent should be carefully applied to the tiny and uneven gaps that may exist between the device and the circuit, especially those areas that are difficult to reach or easily overlooked, such as small cracks on the edge of the device or the snap-on parts of the current sensor itself. These areas are often potential sources of vibration noise and current noise, and their presence may interfere with the accurate measurement of the sensor.

[0010] In step three, the weather resistance and corrosion resistance of the coupling agent in actual use are evaluated by performing accelerated aging operations with reference to the actual environment, and detecting the degradation rate of the magnetic circuit contact surface from the perspective of two-dimensional materials. Specifically, electron microscopy, infrared spectroscopy, Raman spectroscopy and other characterization methods can be used.

[0011] In step three, the cone penetration of the coupling agent is tested to evaluate the hardness of the coupling agent. Cone penetration is a key indicator to measure the hardness of the magnetic coupling agent, and its suitability is directly related to the effect of the coupling agent. Using the standard method, the cone and cone rod assembly is released from the cone penetration meter at room temperature, and the penetration depth of the cone is recorded 5 seconds after it falls. The test is repeated three times to take the average value. By precisely controlling the cone penetration, it is ensured that the coupling agent is neither too soft to cause loss nor too hard to affect the uniformity of spreading, so as to achieve the best magnetic coupling effect while ensuring weather resistance.

[0012] In step three, the temperature stability of the coupling agent is estimated through a dropping point test. The dropping point test is an important means to evaluate the high temperature resistance of the magnetic coupling agent. In the dropping point tester, the coupling agent sample is placed in a continuously rising temperature environment until the moment when the grease drips is observed. The temperature at this time is recorded as the dropping point. The high or low dropping point directly reflects the stability of the coupling agent in a high temperature environment and is an important basis for selecting a coupling agent suitable for application in extreme temperature conditions. The dropping point test ensures that the coupling agent can still maintain the stability of its physical and chemical properties at high temperatures, providing a strong guarantee for the long-term stable operation of the system.

[0013] In step three, use the same current sensor to test the current on the same circuit, set the current size to be the same, one uses coupling agent and the other does not, and the effect of suppressing magnetic circuit noise can be visually seen through an oscilloscope.

[0014] The present invention proposes a method for improving the performance of a current sensor based on a magnetic coupling agent. The method achieves a wide range of adjustments to key mechanical properties such as paste hardness and temperature stability by accurately setting the key mechanical performance indicators of the magnetic coupling agent paste, and finely regulating based on the specific conditions of the actual application environment and the type of sensor magnetic circuit characteristics. At the same time, an environmental adaptability evaluation strategy based on two-dimensional material science characterization technology is introduced to achieve real-time monitoring and optimization of the paste component ratio, ensuring effective suppression of magnetic circuit noise and efficient improvement of the overall performance of the current sensor. This reduction in noise directly improves the measurement accuracy of the current sensor, making the measurement of current parameters more accurate and reliable in a complex and changeable power system environment. Since the magnetic coupling agent paste can be finely regulated according to the actual application environment and the sensor magnetic circuit characteristics, it can better adapt to various working environments, including extreme conditions such as high pressure, low pressure, high temperature, and low temperature. This adaptability not only extends the service life of the sensor, but also significantly improves its long-term stability.

[0015] Compared with the traditional method of improving performance by improving sensor structure design or material optimization, the magnetic coupling agent technology of the present invention does not require complex modification of the sensor or replacement of expensive materials. This not only reduces costs, but also simplifies the implementation process, making the technology easier to promote and apply. The introduction of magnetic coupling agent effect evaluation and mechanical property strength compensation strategy enables the composition ratio of the magnetic coupling agent paste to be monitored and optimized in real time according to the actual working environment and different types of current sensors. This dynamic feedback compensation mechanism ensures that the magnetic circuit noise can be effectively suppressed in different application environments, thereby improving the environmental adaptability and measurement accuracy of most current sensors.

[0016] In summary, the coupled high-precision current sensor magnetic circuit noise suppression method of the present invention shows significant beneficial effects in improving the measurement accuracy and stability of the current sensor, reducing costs and complexity, and improving environmental adaptability, providing important guarantees for the safe and stable operation of the power system. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0018] Figure 1 A flow chart of the method provided by the present invention; Figure 2 The relationship between the dropping point and the graphene content in one embodiment of the present invention; Figure 3 The relationship between the dropping point and the content of the compounded graphene in one embodiment of the present invention; Figure 4 The figure is a comparison diagram of the noise reduction effect in one embodiment of the present invention. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0020] The method for improving the efficiency of inductive power extraction of the present invention is divided into four steps: determining the characteristics of the environment and current sensor type, preparing the magnetic coupling agent and adjusting the mechanical characteristics, testing the coupling agent and evaluating the effect, and compensating the mechanical characteristics of the coupling agent. Step 1: Determine the environmental and current sensor core material characteristics The core material properties and environmental properties used in the current sensor will affect the magnetic circuit coupling effect, so differentiated requirements are put forward for the performance of the magnetic coupling agent. The coupling agent paste must have excellent mechanical stability and temperature stability to withstand the challenges of environmental factors. However, this demand for enhanced stability is often accompanied by a potential reduction in the contact efficiency between the coupling agent and the magnetic core, which may lead to an increase in magnetic resistance. Therefore, for specific application scenarios, it is particularly important to accurately balance and optimize the performance parameters of the magnetic coupling agent and find a range of values ​​that can meet the stability requirements without excessively sacrificing contact efficiency. At the same time, considering the differences in physical properties such as magnetic permeability and saturation characteristics of different core materials, this optimization process also needs to deeply consider the characteristics of the core material to achieve the best magnetic circuit coupling effect.

[0021] Establish a formula for mechanical performance strength, including initial core permeability, maximum core permeability saturation magnetic induction, core cross-sectional area, coercive force, Curie temperature, ambient temperature, and vibration amplitude parameters, and preliminarily calculate the mechanical performance strength of the coupling agent paste. This is used for the characteristic compensation of the coupling agent performance strength later.

[0022] η Where Q is the mechanical strength, η is the efficiency adjustment coefficient, 1 is initially the core magnetic permeability η, 2 Initially, the core permeability, B s is the saturation flux density, S is the core cross-sectional area, H c is the coercivity, T is the ambient temperature, T C is Curie temperature, R is ambient humidity, and A is vibration amplitude.

[0023] Step 2: Preparation of magnetic coupling agent The magnetic coupling agent specially designed for suppressing the noise of the current sensor of the present invention includes a base oil, a thickener, and a conductive filler. The base oil needs to be selected with excellent high temperature resistance and outstanding corrosion resistance. For example, silicone oil can be selected as its core base oil, and a thickener is introduced for thickening treatment. The conductive filler can be ceramic ferrite (this material is synthesized through a precise ceramic process, and the core components are iron oxide, nickel oxide and zinc oxide), graphite, graphene and other high-efficiency conductive fillers.

[0024] After experiments, an ordered data set was established for the magnetic coupling agent, and the binary search method was used to search in the ordered data set (by continuously dividing the search range of the problem into two, gradually narrowing the search range, and eventually finding the solution or approximate solution to the problem), the specific mechanical properties were determined, the filler ratio was adjusted, and finally the magnetic coupling agent was made through mechanical stirring.

[0025] The experiment includes testing of various properties of different coupling agent formula ratios. In some embodiments of the present invention, the following single performance tests are included: (1) Weather resistance and corrosion resistance: Accelerated aging operation is performed with reference to the actual environment, and the degradation rate of the magnetic circuit contact surface is detected from the perspective of two-dimensional materials, such as using electron microscopy, infrared spectroscopy, Raman spectroscopy and other characterization methods.

[0026] (2) Cone penetration: Cone penetration is a key indicator for measuring the hardness of the magnetic coupling agent. Its suitability is directly related to the effect of the coupling agent. Using the standard method, release the cone and cone rod assembly from the cone penetration meter at room temperature, record the penetration depth of the cone 5 seconds after it falls, and repeat the test three times to take the average value. By precisely controlling the cone penetration, it is ensured that the coupling agent is neither too soft to cause loss nor too hard to affect the uniformity of spreading, thereby achieving the best magnetic coupling effect while ensuring weather resistance.

[0027] It can be found that with the increase of filler content, the cone penetration of magnetic coupling agent shows a significant downward trend, from the initial 97.8 to 71.4, a decrease of 26.4%.

[0028] It can be found that under the premise of keeping the thickener and silicone oil matrix unchanged, the filler particle size becomes the key factor affecting the cone penetration. For magnetic coupling agents using 2μm ceramic ferrite, 1000 mesh graphite powder, nano-graphene, and composite graphite and graphene as fillers, the smaller the filler particle size, the larger the specific surface area, which leads to a more significant reduction in cone penetration. This phenomenon fully demonstrates that the particle size and specific surface area of ​​the filler material have a significant regulatory effect on the change trend of the cone penetration of the magnetic coupling agent.

[0029] If the cone penetration is too high (i.e. greater than 90), it means that the viscosity of the magnetic coupling agent is low. In actual outdoor applications, it is easy to lose when applied to the magnetic coupling interface, which seriously affects its high temperature resistance and may cause the magnetic coupling agent to fail. On the contrary, if the magnetic coupling agent is too hard (the cone penetration is less than 70), it is easy to produce bubbles and dry up during the application process, resulting in poor contact at the magnetic coupling interface, increasing contact resistance, and thus damaging the connection quality of the magnetic coupling system. Therefore, accurately measuring and controlling the cone penetration of the magnetic coupling agent to an appropriate range is crucial to ensure its stable performance and efficient operation under various environmental conditions. The appropriate cone penetration can be adjusted by changing the filler content or the size of the filler particle size.

[0030] (3) Temperature stability performance: Perform a dropping point test. The dropping point test is an important means to evaluate the high temperature resistance of magnetic coupling agents. In the dropping point tester, the coupling agent sample is placed in a continuously rising temperature environment until the moment when the grease drips is observed. The temperature at this time is recorded as the dropping point. The dropping point directly reflects the stability of the coupling agent in a high temperature environment and is an important basis for selecting a coupling agent suitable for application under extreme temperature conditions. The dropping point test ensures that the coupling agent can still maintain the stability of its physical and chemical properties at high temperatures, providing a strong guarantee for the long-term stable operation of the system.

[0031] The dropping point can reflect the maximum operating temperature of the magnetic coupling agent to a certain extent. The stronger the high temperature resistance, the more stable the performance of the magnetic coupling agent in a high temperature environment. When the magnetic coupling agent works at a temperature higher than its own limit, it will cause oil and fat separation, resulting in the failure of the magnetic coupling agent. The factors that affect the dropping point size mainly include the performance of the base oil, the performance of the thickener, the performance of the filler, and the control of the preparation process.

[0032] For example, in one embodiment of the present invention, five magnetic coupling agents with different ceramic ferrite contents were prepared, and the high temperature resistance performance of the five magnetic coupling agents was tested. The test results are shown in Table 1.

[0033] Table 1 Relationship between dropping point and ceramic ferrite content The dropping point of the magnetic coupling agent mainly depends on the size of the cone penetration, the interaction between the thickener, the base oil and the filler. The study found that with the increase of the ceramic ferrite content, the dropping point of the magnetic coupling agent first increased sharply, tended to stabilize and then showed a trend of gradual decrease. This is because when the ceramic ferrite content is 77%, the cone penetration is 95.4, which causes the viscosity of the magnetic coupling agent to decrease, making it easy to flow, and the dropping point is only 180°C. When the ceramic ferrite content begins to increase, the silicone oil and thickener inside the magnetic coupling agent interact with each other, increasing the colloid stability and showing better stability. Continuously increasing the ceramic ferrite content, the cone penetration decreases, the grease begins to harden, destroying the colloid stability inside the magnetic coupling agent, and its dropping point drops to 245°C.

[0034] For example, in one embodiment of the present invention, five magnetic coupling agents with different graphene contents were prepared, and the high temperature resistance performance of the five magnetic coupling agents was tested. The test results are shown in Table 2.

[0035] Table 2 Relationship between dropping point and graphene content Figure 2 The graph is a relationship curve between dropping point (℃) and graphene content (wt%). The dropping point of the magnetic coupling agent mainly depends on the size of the cone penetration, the interaction between the thickener, base oil and filler. The study found that with the increase of graphene content, the dropping point of the magnetic coupling agent increased sharply from 260℃ to 330℃, and then gradually decreased to 290℃ after stabilizing. This is because when the graphene content is 3%, the cone penetration is 97.8, and the internal viscosity of the magnetic coupling agent is low and easy to flow. However, because the high temperature resistance of silicone oil itself can reach 200℃, the van der Waals force inside the graphene sheet acts on the inside of the material, making its own toughness and thixotropy stronger than other materials. Affected by the interaction of the thickener, the high temperature resistance of the magnetic coupling agent far exceeds the standard requirements (200℃). With the continuous increase of graphene content, the colloid synergy of stable graphene, phenyl silicone oil and thickener makes the colloidal structure of magnetic coupling agent more stable. When the graphene content is 5%, the high temperature resistance reaches 330℃. The continuous increase of graphene content causes the agglomeration of fillers. At this time, the cone penetration begins to decrease, the magnetic coupling agent becomes hard, and the internal fluidity begins to deteriorate. It is easy to cause oil separation in high temperature environment, and its dropping point drops to 290℃.

[0036] For example, in one embodiment of the present invention, five magnetic coupling agents with different contents of compounded graphene (obtained by compounding 1% graphene and mixing it with ceramic ferrite) were prepared, and the high temperature resistance performance of these five magnetic coupling agents was tested. The test results are shown in Table 2.

[0037] Table 3 Relationship between dropping point and compound graphene content Figure 3 The graph is a graph showing the relationship between the dropping point (°C) and the content of compounded graphene (wt%). The study found that with the increase in the content of compounded graphene, the dropping point of the magnetic coupling agent increased sharply from 250°C to 314°C, gradually stabilized, and then continued to increase to 325°C. This is because when the filler content is 69%, the cone penetration is 95.7, and the internal viscosity of the magnetic coupling agent is low and easy to flow. However, because the high temperature resistance of silicone oil itself can reach 200°C, the stable internal structure of graphene and the thickener work together, and when subjected to high temperature, the dropping point of the magnetic coupling agent can reach 250°C. With the continuous increase in the content of graphene, the colloidal synergy of stable graphene, phenyl silicone oil and thickener continues to strengthen, making the colloidal structure of the magnetic coupling agent more stable. When the filler content is 73%, the cone penetration is reduced to 82.7, which is the optimal viscosity range of the magnetic coupling agent. Therefore, the dropping point shows a trend of continuing to rise. Based on the above experimental results, it can be shown that the dropping point of the magnetic coupling agent can be significantly improved by finely controlling the filler particle size and optimizing the cone penetration range, thereby enhancing its high temperature resistance and overall performance stability in practical applications.

[0038] (4) Effect of noise suppression: Use the same current sensor to test the current on the same circuit, set the current size to be the same, one uses coupling agent and the other does not. The effect of suppressing magnetic circuit noise can be visually seen through an oscilloscope, verifying the actual effect of this method. Figure 4 The figure is a test result of an embodiment of the present invention.

[0039] In some embodiments of the present invention, 2 μm ceramic ferrite, 1000 mesh graphite powder, nano-graphene, and composite graphite and graphene are used as fillers to prepare magnetic coupling agents.

[0040] Step 3: Trial use of magnetic coupling agent and effect evaluation Apply the prepared coupling agent to the contact surface of the current sensor magnetic circuit, and also carefully apply it to the tiny and uneven gaps that may exist between the device and the circuit, especially those areas that are difficult to reach or easily overlooked, such as the small cracks on the edge of the device or the buckle part of the current sensor itself. These areas are often potential sources of vibration noise and current noise, and their presence may interfere with the accurate measurement of the sensor.

[0041] Similarly, the individual tests were completed, and the performance of the coupling agent was comprehensively evaluated. The mechanical strength error ∆e was calculated, and its value was between 0 and 1, which can intuitively reflect the degree of closeness between the actual performance of the coupling agent and the expected target.

[0042] The calculation idea of ​​mechanical property strength error ∆e is as follows: Single performance error = actual test value - expected target value; The weighted average method is used to calculate the comprehensive performance error; According to the importance and weight of each mechanical performance indicator, the weighted average error value is calculated. This can be achieved by the formula: comprehensive performance error = Σ(single performance error × weight) / Σweight. In order to make the value of the mechanical performance strength error ∆e between 0 and 1, it can be normalized, that is, the comprehensive performance error is divided by a suitable reference value. The reference value can be the maximum, minimum or average value of the expected target value, etc., depending on the purpose and requirements of the evaluation.

[0043] The normalized mechanical property strength error ∆e can be calculated using the formula: ∆e = comprehensive performance error / reference value.

[0044] Step 4: Mechanical strength compensation of coupling agent Based on the evaluation results, the mechanical strength compensation of the coupling agent can be performed, and the coupling agent formula can be further optimized to further improve its performance and meet a wider range of application needs. The obtained performance error is added to the established mechanical strength formula to obtain the final mechanical strength of the coupling agent paste.

[0045] in is the adjustment factor, To compensate for the mechanical strength.

[0046] Finally, according to the compensated mechanical performance strength, the coupling agent paste formula is configured through experiments to find the corresponding proportion of formula ingredients.

[0047] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for improving the performance of a current sensor based on a magnetic coupling agent, characterized in that The following steps are involved: Step 1: Preliminarily calculate the mechanical strength of the coupling agent paste based on the environment and the characteristics of the current sensor type. or ; Among them, Q is the mechanical strength, η is the efficiency adjustment coefficient, 1 is initially the core magnetic permeability η, 2 Initially, the core permeability, B s is the saturation flux density, S is the core cross-sectional area, H c is the coercivity, T is the ambient temperature, T C is Curie temperature, R is ambient humidity, A is vibration amplitude Step 2, preparation of magnetic coupling agent: the magnetic coupling agent includes base oil, thickener, and conductive filler. The specific mechanical properties are determined by experiment using dichotomy method to adjust the filler ratio, and finally the magnetic coupling agent is prepared by mechanical stirring; Step 3: Coupling agent trial and effect evaluation: Apply the prepared coupling agent to the contact surface of the magnetic circuit of the current sensor, evaluate the coupling agent's weather resistance, corrosion resistance, hardness, temperature stability, and magnetic circuit noise suppression effect in actual use, and calculate the mechanical strength error ∆e, whose value is between 0 and 1, which can intuitively reflect the degree of closeness between the actual performance of the coupling agent and the expected target; Step 4: Mechanical property compensation of coupling agent: Add the mechanical property strength error ∆e obtained in step 3 to the mechanical property strength formula established in step 1 to obtain the final mechanical property strength of the coupling agent paste. ; in is the adjustment factor, To compensate for the mechanical strength; According to the compensated mechanical property strength, the coupling agent paste formula is configured through experiments to find the proportion of the corresponding formula ingredients.

2. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step 2, the base oil is silicone oil.

3. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step 2, the conductive filler is one or more of ceramic ferrite, graphite, and graphene.

4. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step three, the prepared coupling agent should be carefully applied to the tiny and uneven gaps that may exist between the device and the circuit.

5. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step three, the weather resistance and corrosion resistance of the coupling agent in actual use are evaluated. The specific process is: accelerated aging operation is performed with reference to the actual environment, and the degradation rate of the magnetic circuit contact surface is detected from the perspective of two-dimensional materials.

6. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step three, the hardness of the coupling agent is evaluated by testing the cone penetration of the coupling agent.

7. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step 3, the temperature stability of the coupling agent is evaluated by a dropping point test.

8. The method for improving the performance of a current sensor based on a magnetic coupling agent according to claim 1, characterized in that: In step three, use the same current sensor to test the current on the same circuit, set the current size to be the same, one uses coupling agent and the other does not, and the effect of suppressing magnetic circuit noise can be visually seen through an oscilloscope.

Citation Information

Patent Citations

  • Neodymium-iron-boron magnet crack fracture prediction method based on particle filtering algorithm

    CN112507599A

  • Low-frequency magnetic antenna with compensation function and self-adaptive compensation method

    CN114039189A

  • Multi-purpose magnetic coupling agent based on graphene

    CN119889858A

  • Inductive power taking efficiency improving method based on magnetic coupling

    CN119989614A

  • Non-contact magnetoelectric composite current sensor with magnetism gathering and magnetic shielding

    CN120294393A